Národnostní politika v sovětské Karélii, 1920-1935 - Šebesta, Adam (Univerzita Karlova, Fakulta sociálních věd, 2010)
Diploma thesis "Nationality policy in Soviet Karelia, 1920-1935 " deals with the bolshevik experiment of governing a multinational empire on the example of eastern Karelia in the inter-war period. The paper examines the specific aspects of Karelia's development in contrast with the central nationality policies. Unique region with Finnish communist emigrants as leaders serves as an essence of understanding the nationality policies of the USSR. In search of a large-scale support of all the Russia's peoples the bolsheviks opted for a pragmatic policy of national concessions. The creation of autonomous Karelia was only possible because of a number of factors. Thanks to the policy of building national cadres, the Soviets were temporarily inclined towards regional administration. The success of Tartu peace negotiations was determined by solving the Karelian question and autonomous Karelia seemed to have been just the answer to Finnish demands. The region was supposed to become a showcase of socialism and friendship of the peoples. The Finnish bolsheviks were up to this challenge. Apart from the actual nationality policy in Karelia, the thesis also deals with the factors determining the level of independence such as economic policies and the dependence on center, language and education questions and challenges to. Diplomová práce "Národnostní politika v sovětské Karélii, 1920-1935" pojednává o bolševickém experimentu v oblasti správy multinárodnostní říše na příkladu východní Karélie v meziválečném období. Práce zkoumá specifika karelského vývoje ve srovnání s centrální národnostní politikou. Unikátní region, v jehož čele stáli finští komunističtí emigranti, je v jistém smyslu esencí národnostní politiky SSSR. Ve snaze získat podporu všech národnostní na území Ruska se bolševici uchýlili k pragmatické politice ústupků. Vznik autonomní Karélie byl zapříčiněn součtem faktorů. Díky politice budování národnostních kádrů byli Sověti dočasně nakloněni lokální správě. Mírová jednání s Finskem v Tartu žádala vyřešení ...